CONCEPT AND DEVELOPMENT OF DA'WAH METHODS IN THE ERA OF GLOBALIZATION: KONSEP DAN PENGEMBANGAN METODE DAKWAH DI ERA GLOBALISASI - Agusman A; Muhammad Hanif (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2021)
The da'wah method is a form of discourse and wasilah as symbols and visions and missions of da'wah or a form of amar ma'ruf nahi munkar, which must be distributed to the scope of Muslims and various homogeneous people who are basic and have different knowledge backgrounds and different methods of analyzing material and the messages conveyed by the da'i, both those aimed at the minority community still absorbing the minimal knowledge of various dimensions or vice versa. Da'wah methods and strategies in Islam must be more effective in conveying and transferring various materials or messages of da'wah through various concepts, systems. The method of delivery is done well so that people easily accept it. Islam is the last religion revealed by Allah through Prophet Muhammad SAW. As a da'wah religion, Islam always calls on its people to convey its teachings to others, so that every mature and reasonable Muslim is obliged to carry out this Islamic mission. Da'wah is all activities and activities that invite people to change from a situation that contains non-Islamic values ​​of life to Islamic values ​​of life. These activities and activities are carried out by inviting, encouraging, calling, without pressure, coercion and provocation, and not by persuading and seducing the provision of basic necessities and so on. As exemplified by the Prophet, he always conveyed the revelations he received to be conveyed to his people, in order to perfect human morals. So that the concept and development of da'wah methods in the current era of globalization is very necessary to achieve good and maximum da'wah in society.